Analisis Sistem Akuntansi Pengeluaran Kas Pada KSP Duta Sejahtera - Stephanie Megita Gilberty Nohal; I Nyoman Sunarta; Gusi Putu Lestara Permana (Universitas PGRI Madiun, 2022)
The development of information systems, especially in the accounting field, requires companies to create effective and efficient information to provide financial information transparently to those who need it. To meet the needs of financial information for companies, it is necessary to develop an accounting system. With the implementation of the accounting system in the company, it is expected that all company activities can run well, especially those closely related to the rate of cash flow. One of the problems faced by the company is the internal control of the cash disbursement system. KSP Duta Sejahtera is a cooperative engaged in savings and loan services. At KSP Duta Sejahtera, cash disbursements are made using checks, except for small expenditures that can be made through petty cash. The results obtained indicate that the internal control of the cash disbursement accounting system at KSP Duta Sejahtera has weaknesses, namely that there are still dual functions, namely the accounting function which doubles as a cash function and the function of the internal examiner and does not have a written accounting system guideline. This can lead to embezzlement of cash.